2012
DOI: 10.1007/s10072-011-0925-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves motor deficits and alters striatal GFAP expression in a 6-OHDA-induced rat model of Parkinson’s disease

Abstract: Astrocytic changes have been demonstrated in several neurodegenerative diseases, showing that these cells play an important role in functional recovery/maintenance against brain damage. Physical exercise is known to contribute to this process; however, the cellular mechanisms involved are not fully understood. This study investigated the effects of physical exercise on motor deficits and the expression of glial fibrillary acidic protein (GFAP) in a model of Parkinson's disease (PD). Rats were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 26 publications
2
24
2
7
Order By: Relevance
“…These results may appear to contrast with recent studies in experimental animals and PD patients that demonstrate how performance of movement in the form of physical training and exercise may improve motor deficits and even ameliorate dyskinesias (Goodwin et al, 2008; Döbrössy et al, 2010; Frazzitta et al, 2010; Dutra et al, 2012; Frazzitta et al, 2012; Aguiar et al, 2013). In this regard, it is worth considering that extensive neuroplasticity takes place in the striatum, which regulates movement performance, that physical activity may interfere with these neuroplastic phenomena, eventually influencing the execution of movement at a later time, and that neuroplasticity can be profoundly modified in conditions of dopamine denervation (Tillerson et al, 2001; Packard and Knowlton, 2002; Smith and Zigmond, 2003; Schouenborg, 2004; Graybiel, 2005).…”
Section: Discussioncontrasting
confidence: 78%
“…These results may appear to contrast with recent studies in experimental animals and PD patients that demonstrate how performance of movement in the form of physical training and exercise may improve motor deficits and even ameliorate dyskinesias (Goodwin et al, 2008; Döbrössy et al, 2010; Frazzitta et al, 2010; Dutra et al, 2012; Frazzitta et al, 2012; Aguiar et al, 2013). In this regard, it is worth considering that extensive neuroplasticity takes place in the striatum, which regulates movement performance, that physical activity may interfere with these neuroplastic phenomena, eventually influencing the execution of movement at a later time, and that neuroplasticity can be profoundly modified in conditions of dopamine denervation (Tillerson et al, 2001; Packard and Knowlton, 2002; Smith and Zigmond, 2003; Schouenborg, 2004; Graybiel, 2005).…”
Section: Discussioncontrasting
confidence: 78%
“…; Dutra et al . ). Amelioration of parkinsonian‐like symptoms may also be elicited by the performance of voluntary exercise, as indicated by studies showing that 6‐OHDA‐lesioned rats allowed access to a running wheel exhibited scarce contralateral rotational behavior in response to apomorphine, compared with sedentary hemiparkinsonian rats (Mabandla et al .…”
Section: Link Between Motor Performance Physical Activity and Dyskinmentioning
confidence: 97%
“…Studies on the effect of exercise in animal models of PD have indicated that exercise not only protects dopaminergic neurons from the toxic effects of neurotoxins (1-methyl-4-phenyl-1,2,3,6-tetrahydro-pyridine, MPTP), but also improves cognitive function in the neurotoxin treated animals. Although, exercise has no effect on tyrosine hydroxylase immunoreactivity in striatum, but it restores striatal GFAP expression (Dutra et al 2012). Recent studies have also indicated that exercise in the form of intensive treadmill running facilitates neuroplasticity through increased expression of striatal dopamine D2 receptors (DA-D2Rs), a process most evident in the MPTP-mediated injured brain (Vuckovic et al 2010).…”
Section: Effects Of Exercise In Animal Models Of Parkinson Diseasementioning
confidence: 97%